Ectopia cordis about a case at Ourossogui regional hospital center - Diakhate, Abdoulaye; Guèye, Mame D. N.; Diallo, Abdou K.; Wade, Mouhamadou; Ndour, Simon B.; Diop, Daba; Dieng, Cheikh; Mbodji, Ameth; Guèye, Mamour (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
We report in this work, an extremely rare and major case of anterior body wall defects included ectopia cordis define by abnormal location of heart outside of the thorax. This case was diagnosed at the maternity of Ourossogui regional hospital center, in Senegal. Any scan was performed during the pregnancy. Newborn died 10 minutes after birth. Ectopia cordis is related to a possible ventral midline developmental abnormality. It’s associated to other midline abnormalities and is a part of pentalogy of Cantrell. An X-linked genetic abnormality.